2002
DOI: 10.1097/00002060-200210000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Type A Use in Piriformis Muscle Syndrome

Abstract: VAS data suggest that intramuscular piriformis injection with 100 units of botulinum toxin type A can reduce pain to a greater extent than similar injections with vehicle alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
9

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(82 citation statements)
references
References 25 publications
1
72
0
9
Order By: Relevance
“…Previous clinical reports addressing piriformis syndrome have focused on multiple, concurrent treatment interventions and have emphasized stretching, 1,11,15,16,19,26,27,30 soft tissue mobilization, 1,5,11,15,16,19,30 electrophysical agents, 1,5,11,16,19 and medication and injections. 1,3,5,8,11,15,16,26,27,30 The overriding premise behind such interventions is that a shortened piriformis is responsible for creating compression on the sciatic nerve. 5,9,11,15,27,29,33 Although 2 previous authors addressed hip abductor weakness and 1 author noted that hip abductor strengthening "seemed to hasten recovery," 1,17 these authors offered no mechanism as to why strengthening would be effective.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous clinical reports addressing piriformis syndrome have focused on multiple, concurrent treatment interventions and have emphasized stretching, 1,11,15,16,19,26,27,30 soft tissue mobilization, 1,5,11,15,16,19,30 electrophysical agents, 1,5,11,16,19 and medication and injections. 1,3,5,8,11,15,16,26,27,30 The overriding premise behind such interventions is that a shortened piriformis is responsible for creating compression on the sciatic nerve. 5,9,11,15,27,29,33 Although 2 previous authors addressed hip abductor weakness and 1 author noted that hip abductor strengthening "seemed to hasten recovery," 1,17 these authors offered no mechanism as to why strengthening would be effective.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,5,8,11,15,16,26,27,30 The overriding premise behind such interventions is that a shortened piriformis is responsible for creating compression on the sciatic nerve. 5,9,11,15,27,29,33 Although 2 previous authors addressed hip abductor weakness and 1 author noted that hip abductor strengthening "seemed to hasten recovery," 1,17 these authors offered no mechanism as to why strengthening would be effective. After a review of the published literature, no studies were found that mentioned our proposed mechanism of injury or treatment approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Botulinum toxin injections in PS 14,21,29,35,48,84,87,90,[102][103][104] Botulinum toxin type A is one of seven immunologically distinct serotypes (A-G) of neurotoxin produced by Clostridium botulinum. Botulinum toxin type A can be administered with fluoroscopic, electromyelographic, CT, or MRI guidance.…”
Section: Injection Solutionmentioning
confidence: 99%